A122 CANADIAN STUDY OF ADHERENCE OUTCOMES IN HUMIRA® (ADALIMUMAB) PATIENTS: THREE-YEAR RESULTS FROM THE COMPANION STUDY IN GASTROENTEROLOGY PATIENTS. (1st March 2018) - Marshall, J; Lebovic, G; Millson, B; Sung, M; Gaetano, T; Latour, M; Laliberte, M
Abstract: Background: HUMIRA ® (adalimumab, ADA) is a TNF-alpha inhibitor indicated for inflammatory autoimmune diseases including Crohn's disease (CD) and ulcerative colitis (UC). Patients receiving ADA in Canada can enroll in the AbbVie Care patient support program (PSP) providing personalized services. Aims: This retrospective study assessed the impact of specific factors, including PSP services and patient characteristics, on persistence and adherence to ADA over a 3-year period in the overall cohort (all indications) and in CD and UC patients specifically. Methods: ADA PSP patients were linked to the IMS longitudinal pharmacy transaction database using a probabilistic matching algorithm. Patients starting ADA between July 2010 and August 2012 were indexed and tracked for 36 months to calculate days until end of persistence (>90 days without therapy), censored for persistence through month 36. Cox regressions and multivariable logistic regression models provided hazard ratios (HR) and adjusted odds ratios (OR) to measure the association between patient characteristics/PSP services and persistence and adherence, respectively. Adherence was measured using the medication possession ratio (MPR) (≥80% MPR). Additional analyses were done in patients who were persistent up to when specific PSP services were introduced in a separate cohort. Results: A final sample of 4, 772 patients (including 1, 921 CD and 108 UC patients) was selected. In the overall cohort, older age groups had significantly greater odds of adherence (40–49, 50–59, 60–69, 70+; OR=1.3, 1.4, 1.4, 2.1; p<0.05 for all comparisons) relative to the 30–39 years age group. In a subset of patients (n=2, 866) who were persistent when ongoing care coach calls were available, those receiving this service were 65% less likely to stop therapy (HR=0.35, p<0.01) and 38% more adherent (OR = 1.38, p<0.01) compared to those without it. Among this patient subset, CD and UC patients (n=1, 321) who received this service were 53% more persistent (HR=0.47, p<0.01) and 45% more adherent (OR=1.45, p<0.05) compared to those without it. Conclusions: Ongoing care coach calls provided by the AbbVie Care PSP significantly correlate with greater patient persistence and adherence over 36 months. These results may help refine services that improve treatment adherence. Funding Agencies: AbbVie